Pola Komunikasi Pondok Pesantren Al-Mukhlisin dalam Membangun Citra Positif di Kabupaten Batu Bara - Husnah, Lutfiah (Darul Yasin Al Sys, 2024)
This research aims to analyze the communication patterns used by the Al-Mukhlisin Islamic Boarding School in an effort to build a positive image in Batu Bara Regency. This research method uses a descriptive method with a qualitative approach. In this approach, the author directly deals with respondents to collect the required information data, both from the location, head of the foundation, administrators or teachers and activities that occurred while conducting research. The research results show that the communication pattern applied in building a positive image of the Al-Mukhlisin Islamic Boarding School in Batu Bara Regency is a direct interpersonal communication pattern. This Islamic boarding school builds a positive image individually. In the initial phase of its establishment, Al-Mukhlisin Islamic Boarding School introduced itself by using banners, distributing brochures, and sending children to give lectures in prayer rooms or mosques every month of Ramadan. This is one of the attractions for the local community to be interested in this Islamic Boarding School. The obstacle lies in the fact that this Islamic boarding school does not have selling rights, in the sense that they introduced this Islamic boarding school when other schools were already established, making it difficult to compete because they had not seen Al-Mukhlisin's educational process.